Human and Murine Innate Immune Cell Populations Display Common and Distinct Response Patterns during Their In Vitro Interaction with the Pathogenic Mold Aspergillus fumigatus - Hellmann, Anna-Maria; Lother, Jasmin; Wurster, Sebastian; Lutz, Manfred B.; Schmitt, Anna Lena; Morton, Charles Oliver; Eyrich, Matthias; Czakai, Kristin; Einsele, Hermann; Loeffler, Juergen (Frontiers in Immunology, 2017)
Aspergillus fumigatus is the main cause of invasive fungal infections occurring almost exclusively in immunocompromised patients. An improved understanding of the initial innate immune response is key to the development of better diagnostic tools and new treatment options. Mice are commonly used to study immune defense mechanisms during the infection of the mammalian host with A. fumigatus. However, little is known about functional differences between the human and murine immune response against this fungal pathogen. Thus, we performed a comparative functional analysis of human and murine dendritic cells, macrophages and polymorphonuclear cells using standardized and reproducible working conditions, laboratory protocols and readout assays. A. fumigatus did not provoke identical responses in murine and human immune cells but rather initiates relatively specific responses. While human DCs showed a significantly stronger upregulation of their maturation markers and MHC molecules and phagocytosed A. fumigatus more efficiently compared to their murine counterparts, murine PMNs and macrophages exhibited a significantly stronger release of reactive oxygen species after exposure to A. fumigatus. For all studied cell types, human and murine samples differed in their cytokine response to conidia or germ tubes of A. fumigatus. Furthermore, Dectin-1 showed inverse expression patterns on human and murine DCs after fungal stimulation. These specific differences should be carefully considered and highlight potential limitations in the transferability of murine host-pathogen interaction studies.